A Contrastive Analysis between English and Indonesian Noun Phrases in The Utterances of The Character “Killmonger” in The Movie “Black Panther 2018” - Okky Ramadhan; Jumanto Jumanto (Universitas Brawijaya, 2019)
The movie “Black Panther (2018)” was directed by Ryan Coogler and starred Chadwick Boseman (T’Challa), and Michael B Jordan (Erik Killmonger). It is a movie based on the Marvel Comics and set in the fictional African nation of Wakanda. Using descriptive qualitative method, this Thesis entitled “A Contrastive Analysis Between English and Indonesian Noun Phrases in The Utterances of The Character ‘Killmonger’ In The Movie ‘Black Panther 2018’”, was done to find out similarities and differences between English and Indonesian Noun Phrases through a contrastive analysis according to Jumanto (2017), in which selection and description are made in table form and below the table, the comparison, prediction and verification of lay translators learning problems are made. Furthermore, the noun phrases were categorized by the arrangement of modifiers as Standard Noun Phrases. This is a construction where the arrangement of modifiers is found around the noun headword. Constructions include, Head + Modifier, Modifier + Head, and Modifier + Head + Modifier. After a contrastive analysis, we have found out now that noun phrases in English and Indonesian are similar constructions except for a few cases. In this research, 100 data of noun phrases were discovered from the utterances of “Killmonger.” Most English noun phrases are structured M+H where the modifier are usually before the noun headword. Its Indonesian counterparts are of opposite constructions H+M. This shows that modifiers in the Indonesian noun phrase are mostly found after the noun headword. While most of the modifiers in both languages are similar, in the Indonesian language, there is a unique modifier in form of a suffix. Nevertheless, when translated, both noun phrases have similar meaning but slightly different constructions i.e. Your ancestors (M+H) – Leluhurmu (H+M), Panther claws in his chest (M+H+M) – Cakar panther di dadanya (H+M)